Correlates of poor mental health in early pregnancy in obese European women - Matteo C. Sattler; Judith G. M. Jelsma; Annick Bogaerts; David Simmons; Gernot Desoye; Rosa Corcoy; Juan M. Adelantado; Alexandra Kautzky-Willer; Jürgen Harreiter; Frans A. van Assche; Roland Devlieger; Goele Jans; et al. (BMC, 2017)
Abstract Background Depression during pregnancy is associated with higher maternal morbidity and mortality, and subsequent possible adverse effects on the cognitive, emotional and behavioral development of the child. The aim of the study was to identify maternal characteristics associated with poor mental health, in a group of overweight/obese pregnant women in nine European countries, and thus, to contribute to better recognition and intervention for maternal depression. Methods In this cross-sectional observational study, baseline data from early pregnancy (< 20 weeks) of the DALI (Vitamin D and Lifestyle Intervention for gestational diabetes mellitus prevention) study were analyzed. Maternal mental health was assessed with the World Health Organization Well-Being Index (WHO-5). Women were classified as having a low (WHO-5 ≤ 50) or high wellbeing. Results. A total of 735 pregnant women were included. The prevalence of having a low wellbeing was 27.2%, 95% CI [24.0, 30.4]. Multivariate analysis showed independent associations between low wellbeing and European ethnicity, OR = .44, 95% CI [.25, .77], shift work, OR = 1.81, 95% CI [1.11, 2.93], insufficient sleep, OR = 3.30, 95% CI [1.96, 5.55], self-efficacy, OR = .95, 95% CI [.92, .98], social support, OR = .94, 95% CI [.90, .99], and pregnancy-related worries (socioeconomic: OR = 1.08, 95% CI [1.02, 1.15]; health: OR = 1.06, 95% CI [1.01, 1.11]; relationship: OR = 1.17, 95% CI [1.05, 1.31]). Conclusions Mental health problems are common in European overweight/obese pregnant women. The identified correlates might help in early recognition and subsequent treatment of poor mental health problems during pregnancy. This is important to reduce the unfavorable effects of poor mental health on pregnancy outcomes. Trial registration ISRCTN70595832 , 02.12.2011.